Feasibility of utilizing the SD BIOLINE Onchocerciasis IgG4 rapid test in onchocerciasis surveillance in Senegal. - Yakou Dieye; Helen L Storey; Kelsey L Barrett; Emily Gerth-Guyette; Laura Di Giorgio; Allison Golden; Dunia Faulx; Michael Kalnoky; Marie Khemesse Ngom Ndiaye; Ngayo Sy; Malang Mané; Babacar Faye; et al. (Public Library of Science (PLoS), 2017)
As effective onchocerciasis control efforts in Africa transition to elimination efforts, different diagnostic tools are required to support country programs. Senegal, with its long standing, successful control program, is transitioning to using the SD BIOLINE Onchocerciasis IgG4 (Ov16) rapid test over traditional skin snip microscopy. The aim of this study is to demonstrate the feasibility of integrating the Ov16 rapid test into onchocerciasis surveillance activities in Senegal, based on the following attributes of acceptability, usability, and cost. A cross-sectional study was conducted in 13 villages in southeastern Senegal in May 2016. Individuals 5 years and older were invited to participate in a demographic questionnaire, an Ov16 rapid test, a skin snip biopsy, and an acceptability interview. Rapid test technicians were interviewed and a costing analysis was conducted. Of 1,173 participants, 1,169 (99.7%) agreed to the rapid test while 383 (32.7%) agreed to skin snip microscopy. The sero-positivity rate of the rapid test among those tested was 2.6% with zero positives 10 years and younger. None of the 383 skin snips were positive for Ov microfilaria. Community members appreciated that the rapid test was performed quickly, was not painful, and provided reliable results. The total costs for this surveillance activity was $22,272.83, with a cost per test conducted at $3.14 for rapid test, $7.58 for skin snip microscopy, and $13.43 for shared costs. If no participants had refused skin snip microscopy, the total cost per method with shared costs would have been around $16 per person tested. In this area with low onchocerciasis sero-positivity, there was high acceptability and perceived value of the rapid test by community members and technicians. This study provides evidence of the feasibility of implementing the Ov16 rapid test in Senegal and may be informative to other country programs transitioning to Ov16 serologic tools.